Synchronizing commercial maturity and enhancing organoleptic quality in table grape through hormonal and metabolic mediation induced by foliar sorbitol‑calcium - Guirao, Alberto; Alamar, M. Carmen; Solana-Guilabert, Ander; Valero, Daniel; Albert-Bermejo, Alejandra María; García-Pastor, María E.; Valverde, Juan Miguel; Martínez-Romero, Domingo (Elsevier, 2026)
The table grape industry faces significant challenges regarding the organoleptic quality of early-season white seedless varieties, which often exhibit neutral aromatic profiles. This study evaluated the impact of foliar applications of 2.5% sorbitol, 0.7% calcium nitrate, and their combined complex (Sor-Ca) in ‘Ivory™’ grapes. We aimed to determine how these treatments modulate the hormonal balance, specifically abscisic acid (ABA) homeostasis, to address these physiological gaps. Results showed that Sor-Ca treatment altered harvest distribution by accelerating the ripening process, leading to a nearly two-fold increase in the proportion of fruit harvested during the initial harvest pass compared to the control, without affecting total cumulative yield. At commercial maturity, treated berries reached significantly higher sugar and phenolic levels. This metabolic shift was accompanied by an increase in total terpene concentration, primarily driven by gains in β-pinene, β-myrcene, and d -limonene. Hormonal profiling confirmed that these changes were linked to significantly higher active ABA levels and a 71% reduction in the inactive storage form, ABA-GE. These findings indicate that the Sor-Ca complex acts as a metabolic elicitor in ‘Ivory™’ table grapes, triggering the mobilization of hormonal reserves to synchronize sugar accumulation with aromatic maturation.
Keywords: 30 Agricultural, Veterinary and Food Sciences; 3008 Horticultural Production; Food Science; 3006 Food sciences; 3210 Nutrition and dietetics; 4004 Chemical engineering; Vitis vinifera L.; Fruit quality; Volatile organic compounds; Abscisic acid; Plant growth regulators; Aromatic compounds